Multiplex PCR and RPLA detection of enterotoxins in Staphylococcus aureus strains isolated from milk, dairy products and human faecal samples - Ossiprandi, Maria Cristina; Zerbini, Laura (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Staphylococcus aureus is considered the worlds third most important cause of food-borne illnesses, of which foods of animal origin, especially milk and dairy products, are responsible. Many S. aureus strains can produce one or more of enterotoxins (SEs), that are recognized agents of intoxication staphylococcal food-borne syndrome but may be also involved in other types of infections with sequelae of shock in humans and animals. The aim of this research was to detect classical staphylococcal SE genes (sea to see) by multiplex PCR and to reveal toxin in vitro production by reversed passive latex agglutination (RPLA) in 258 S. aureus isolates from milk and dairy products of mastitic bovines and from human diarrhoeic faecal samples. Staphylococcal enterotoxin genes were detected in 84 isolates: 34 strains were sea+, 4 seb+, 13 sec+, 20 sed+, 11 sea+sed+, and 2 sec+sed+. Equivocal result was obtained by RPLA for 4 of the 84 strains tested, relatively to SEA and SED. Our results prove that multiplex PCR is the preferential choose to characterize the toxigenicity of S. aureus strains and could complete efficaciously the conventional laboratory diagnosis by increasing its sensibility.